First application of the Laser Ion Source and Trap (LIST) for on-line experiments at ISOLDE - Fink, Daniel; Richter, S. D.; Bastin, B.; Blaum, Klaus; Catherall, R.; Cocolios, T. E.; Fedorov, D. V.; Fedosseev, V. N.; Flanagan, K. T.; Ghys, L.; Gottberg, A.; Imai, N.; et al. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
The Laser Ion Source and Trap (LIST) provides a new mode of operation for the resonance ionization laser ion source (RILIS) at ISOLDE/CERN, reducing the amount of surface-ionized isobaric contaminants by up to four orders of magnitude. After the first successful on-line test at ISOLDE in 2011 the LIST was further improved in terms of efficiency, selectivity, and reliability through several off-line tests at Mainz University and at ISOLDE. In September 2012, the first on-line physics experiments to use the LIST took place at ISOLDE. The measurements of the improved LIST indicate more than a twofold increase in efficiency compared to the LIST of the 2011 run. The suppression of surface-ionized francium contaminants has enabled the first in-source laser spectroscopy of 217Po and 219Po.